THE ROLE OF GOVERNANCE IN THE PERFORMANCE OF ISLAMIC BANKS, A CASE RESEARCH IN IRAQ - Hayder Ali Kadhim Alfatlawi; Wasan Khifah Abdulridha Alsaedi (Scholar Express Journals, 2022)
The research aimed to try to find links among the rules of governance. The research dealt with the advantages of co. After talking about its importance in the banking sector in general, governance in Islamic banks and then measuring the impact of applying governance rules on financial performance on a sample of Islamic banks in Iraq from 2016 to 2020. The researchers used the descriptive and statistical approaches, they used the first to present and discuss the theoretical side, then they used the appropriate statistical analyzes like the T-test One to examine and analyze the data. And the researchers terminated: There is a correlation between the usage of governance rules and the financial performance of the Islamic banks under research. The results showed a (positive) correlation among the return on property and each of the composition of the assembly of directorship, the size of the assembly of directorship, the number of committees in the assembly, and the number of assembly members. Sharia Supervisory Assembly. The greater the size of the indirect variable (the rules of governance), the greater the return on property (the redirect variable), while it is clear that there is a negative correlation between the return on property and the variable of concentration of ownership
Keywords: Governance; Islamic banks; Islamic banks in Iraq; financial performance